This action might not be possible to undo. Are you sure you want to continue?
1
−5 −4 −3 −2 −1 0 1 2 3 4 5
V
in
(mV)
−2
−1
0
1
2
V
o
u
t
(
V
)
8.11
V
−
= V
+
= V
in
V
−
=
R
4
(R
2
+R
3
)
R
1
+R
4
(R
2
+R
3
)
R
2
R
2
+R
3
V
out
= V
in
V
out
V
in
=
R
4
(R
2
+R
3
)
R
1
+R
4
(R
2
+R
3
)
R
2
R
2
+R
3
−1
=
(R
2
+R
3
) [R
1
+R
4
(R
2
+ R
3
)]
R
2
[R
4
(R
2
+R
3
)]
If R
1
→ 0, we expect the result to be:
V
in
=
R
2
R
2
+R
3
V
out
V
out
V
in
R1=0
=
R
2
+R
3
R
2
= 1 +
R
3
R
2
Taking limit of the original expression as R
1
→ 0, we have:
lim
R1→0
(R
2
+R
3
) [R
1
+R
4
(R
2
+R
3
)]
R
2
[R
4
(R
2
+R
3
)]
=
(R
2
+R
3
) [R
4
(R
2
+R
3
)]
R
2
[R
4
(R
2
+R
3
)]
= 1 +
R
3
R
2
This agrees with the expected result. Likewise, if R
3
→ 0, we expect the result to be:
V
in
=
R
2
R
4
R
1
+R
2
R
4
V
out
V
out
V
in
R3=0
=
R
1
+R
2
R
4
R
2
R
4
= 1 +
R
1
R
2
R
4
Taking the limit of the original expression as R
3
→ 0, we have:
lim
R3→0
(R
2
+R
3
) [R
1
+R
4
(R
2
+R
3
)]
R
2
[R
4
(R
2
+R
3
)]
=
R
2
(R
1
+R
2
R
4
)
R
2
(R
2
R
4
)
=
R
1
+R
2
R
4
R
2
R
4
= 1 +
R
1
R
2
R
4
This agrees with the expected result.
8.14 We need to derive the closedloop gain of the following circuit:
−
v
in
+
R
2
+
v
X
−
R
1
v
out
R
out
−
−A
0
v
X
+
v
X
= (v
out
−v
in
)
R
2
R
1
+R
2
+v
in
v
out
= (−A
0
v
X
−v
in
)
R
1
+R
2
R
out
+R
1
+R
2
+v
in
=
−A
0
(v
out
−v
in
)
R
2
R
1
+R
2
+v
in
−v
in
R
1
+R
2
R
out
+R
1
+R
2
+v
in
Grouping terms, we have:
v
out
1 +A
0
R
2
R
1
+R
2
R
1
+R
2
R
out
+R
1
+R
2
= v
in
R
1
+R
2
R
out
+R
1
+R
2
A
0
R
2
R
1
+R
2
−A
0
−1 +
R
out
+R
1
+R
2
R
1
+R
2
= v
in
R
1
+R
2
R
out
+R
1
+R
2
R
out
+R
1
+R
2
R
1
+R
2
−A
0
R
1
R
1
+R
2
−1
= v
in
1
R
out
+R
1
+R
2
[R
out
+R
1
+R
2
−A
0
R
1
−R
1
−R
2
]
= v
in
1 −
A
0
R
1
+R
1
+R
2
R
out
+R
1
+R
2
v
out
v
in
=
1 −
A0R1+R1+R2
Rout+R1+R2
1 +
A0R2
Rout+R1+R2
=
R
out
+R
1
+R
2
−A
0
R
1
−R
1
−R
2
R
out
+R
1
+R
2
+A
0
R
2
=
R
out
−A
0
R
1
R
out
+R
1
+ (1 +A
0
) R
2
To ﬁnd the output impedance, we must ﬁnd Z
out
=
vt
it
for the following circuit:
R
2
+
v
X
−
R
1
i
t
−
v
t
+
R
out
−
−A
0
v
X
+
i
t
=
v
t
+A
0
v
X
R
out
+
v
t
R
1
+R
2
v
X
=
R
2
R
1
+R
2
v
t
i
t
=
v
t
+A
0
R2
R1+R2
v
t
R
out
+
v
t
R
1
+R
2
= v
t
1
R
out
+
A
0
R
2
R
out
(R
1
+R
2
)
+
1
R
1
+R
2
= v
t
R
1
+ (1 +A
0
) R
2
+R
out
R
out
(R
1
+R
2
)
Z
out
=
v
t
i
t
=
R
out
(R
1
+R
2
)
R
1
+ (1 +A
0
) R
2
+R
out
8.15 Refer to the analysis for Fig. 8.42.
V
out
V
in
=
R
1
R
2
= 4
R
in
≈ R
2
= 10 kΩ
R
1
= 4R
2
= 40 kΩ
From Eq. (8.99), we have
E = 1 −
A
0
−
Rout
R1
1 +
Rout
R2
+A
0
+
R1
R2
A
0
= 1000
R
out
= 1 kΩ
E = 0.51 %
8.17
V
+
= V
−
(since A
0
= ∞)
V
in
R
2
= −
V
out
R
3
R
3
R
4
R
1
+R
3
R
4
V
out
V
in
= −
R
3
R
2
R
1
+R
3
R
4
R
3
R
4
If R
1
→0 or R
3
→0, we expect the ampliﬁer to reduce to the standard inverting ampliﬁer.
V
out
V
in
R1→0
= −
R
3
R
2
V
out
V
in
R3→0
= −
R
1
R
2
The gain reduces to the expected expressions.
8.18
V
+
= V
−
(since A
0
= ∞)
V
X
=
R
3
R
3
+R
4
V
out
=
R
2
R
1
+R
2
(V
out
−V
in
) +V
in
V
out
R
3
R
3
+R
4
−
R
2
R
1
+R
2
= V
in
1 −
R
2
R
1
+R
2
V
out
R
3
(R
1
+R
2
) −R
2
(R
3
+R
4
)
(R
1
+R
2
) (R
3
+R
4
)
= V
in
R
1
R
1
+R
2
V
out
V
in
=
R
1
(R
3
+R
4
)
R
3
(R
1
+R
2
) −R
2
(R
3
+R
4
)
8.22 We must ﬁnd the transfer function of the following circuit:
−
v
in
+
R
1
R
in
+
v
X
−
C
1
v
out
−
−A
0
v
X
+
v
out
= −A
0
v
X
v
X
= v
out
−
1
sC
1
v
X
R
in
+
v
X
−v
in
R
1
v
X
1 +
1
sR
in
C
1
+
1
sR
1
C
1
= v
out
+
v
in
sR
1
C
1
v
X
=
sR
1
R
in
C
1
v
out
+R
in
v
in
sR
1
R
in
C
1
+R
1
+R
in
v
out
= −A
0
sR
1
R
in
C
1
v
out
+R
in
v
in
sR
1
R
in
C
1
+R
1
+R
in
v
out
1 +A
0
sR
1
R
in
C
1
sR
1
R
in
C
1
+R
1
+R
in
= −A
0
v
in
R
in
sR
1
R
in
C
1
+R
1
+R
in
v
out
v
in
=
−A
0
R
in
sR
1
R
in
C
1
+R
1
+R
in
·
sR
1
R
in
C
1
+R
1
+R
in
sR
1
R
in
C
1
+R
1
+R
in
+sR
1
R
in
C
1
A
0
=
−A
0
R
in
sR
1
R
in
C
1
+R
1
+R
in
+sR
1
R
in
C
1
A
0
=
−A
0
R
in
sR
1
R
in
C
1
(1 +A
0
) + R
1
+R
in
=
−A
0
R
in
1 +s
R1RinC1(1+A0)
R1+Rin
=
−A
0
R
in
/ (R
1
+R
in
)
1 +s (R
1
R
in
) C
1
(1 +A
0
)
s
p
= −
1
(R
1
R
in
) C
1
(1 +A
0
)
Comparing this to the result in Eq. (8.37), we can see that we can simply replace R
1
with R
1
R
in
,
eﬀectively increasing the pole frequency (since R
1
R
in
< R
1
for ﬁnite R
in
).
We can also write the result as
s
p
= −
1
R
1
C
1
(1 +A
0
)
1 +
R
1
R
in
In this form, it’s clear that the pole frequency increases by 1 +R
1
/R
in
.
8.23 We must ﬁnd the transfer function of the following circuit:
−
v
in
+
R
1
+
v
X
−
C
1
v
out
R
out
−
−A
0
v
X
+
v
out
= −A
0
v
X
+
v
in
−v
out
R
1
+
1
sC1
R
out
v
X
= v
in
+
R
1
R
1
+
1
sC1
(v
out
−v
in
)
v
out
= −A
0
v
in
+
R
1
R
1
+
1
sC1
(v
out
−v
in
)
+
v
in
−v
out
R
1
+
1
sC1
R
out
v
out
1 +
A
0
R
1
+R
out
R
1
+
1
sC1
= v
in
−A
0
+
A
0
R
1
+R
out
R
1
+
1
sC1
v
out
R
1
+
1
sC1
+A
0
R
1
+R
out
R
1
+
1
sC1
= v
in
−A
0
R
1
−A
0
1
sC1
+A
0
R
1
+R
out
R
1
+
1
sC1
v
out
{1 +sC
1
[(1 +A
0
) R
1
+R
out
]} = −v
in
{A
0
−sC
1
R
out
}
v
out
v
in
= −
A
0
−sC
1
R
out
1 +sC
1
[(1 +A
0
) R
1
+R
out
]
s
p
= −
1
C
1
[(1 + A
0
) R
1
+R
out
]
Comparing this to the result in Eq. (8.37), we can see that the pole gets reduced in magnitude due to
R
out
.
8.26 We must ﬁnd the transfer function of the following circuit:
−
v
in
+
C
1
R
in
+
v
X
−
R
1
v
out
−
−A
0
v
X
+
v
out
= −A
0
v
X
v
X
=
_
(v
in
−v
X
) sC
1
−
v
X
−v
out
R
1
_
R
in
v
X
_
1 +sR
in
C
1
+
R
in
R
1
_
= v
in
sR
in
C
1
+v
out
R
in
R
1
v
X
=
v
in
sR
in
C
1
+v
out
Rin
R1
1 +sR
in
C
1
+
Rin
R1
v
out
= −A
0
v
in
sR
in
C
1
+v
out
Rin
R1
1 +sR
in
C
1
+
Rin
R1
v
out
_
1 +
A
0
Rin
R1
1 +sR
in
C
1
+
Rin
R1
_
= −v
in
sR
in
C
1
A
0
1 +sR
in
C
1
+
Rin
R1
v
out
_
1 +sR
in
C
1
+ (1 +A
0
)
Rin
R1
1 +sR
in
C
1
+
Rin
R1
_
= −v
in
sR
in
C
1
A
0
1 +sR
in
C
1
+
Rin
R1
v
out
_
1 +sR
in
C
1
+ (1 +A
0
)
R
in
R
1
_
= −v
in
sR
in
C
1
A
0
v
out
v
in
= −
sR
1
R
in
C
1
A
0
R
1
+sR
1
R
in
C
1
+ (1 +A
0
) R
in
lim
A0→∞
v
out
v
in
= −sR
1
C
1
Comparing this to Eq. (8.42), we can see that if we let A
0
→ ∞, the result actually reduces to Eq.
(8.42).
8.27 We must ﬁnd the transfer function of the following circuit:
−
v
in
+
C
1
+
v
X
−
R
1
v
out
R
out
−
−A
0
v
X
+
v
out
= −A
0
v
X
+
v
in
−v
out
R
1
+
1
sC1
R
out
v
X
= v
in
+
1
sC1
R
1
+
1
sC1
(v
out
−v
in
)
v
out
= −A
0
_
v
in
+
1
sC1
R
1
+
1
sC1
(v
out
−v
in
)
_
+
v
in
− v
out
R
1
+
1
sC1
R
out
v
out
_
1 +
A
0
1
sC1
+R
out
R
1
+
1
sC1
_
= v
in
_
−A
0
+
A
0
1
sC1
+R
out
R
1
+
1
sC1
_
v
out
R
1
+
1
sC1
+A
0
1
sC1
+R
out
R
1
+
1
sC1
= v
in
−A
0
R
1
−A
0
1
sC1
+A
0
1
sC1
+ R
out
R
1
+
1
sC1
v
out
{1 +A
0
+sC
1
(R
1
+R
out
)} = −v
in
{sC
1
(A
0
R
1
−R
out
)}
v
out
v
in
= −
sC
1
(A
0
R
1
−R
out
)
1 +A
0
+sC
1
(R
1
+R
out
)
lim
A0→∞
v
out
v
in
= −sR
1
C
1
Comparing this to Eq. (8.42), we can see that if we let A
0
→ ∞, the result actually reduces to Eq.
(8.42).
8.28
v
out
= −A
0
v
−
v
−
= v
in
+ (v
out
−v
in
)
1
sC1
R
1
_
1
sC1
R
1
_
+
_
1
sC2
R
2
_
v
out
= −A
0
_
_
v
in
+ (v
out
−v
in
)
1
sC1
R
1
_
1
sC1
R
1
_
+
_
1
sC2
R
2
_
_
_
v
out
_
_
1 +A
0
1
sC1
R
1
_
1
sC1
R
1
_
+
_
1
sC2
R
2
_
_
_
= −v
in
A
0
_
_
1 −
1
sC1
R
1
_
1
sC1
R
1
_
+
_
1
sC2
R
2
_
_
_
v
out
_
1
sC1
R
1
_
+
_
1
sC2
R
2
_
+A
0
_
1
sC1
R
1
_
_
1
sC1
R
1
_
+
_
1
sC2
R
2
_ = −v
in
A
0
_
1
sC1
R
1
_
+
_
1
sC2
R
2
_
−
_
1
sC1
R
1
_
_
1
sC1
R
1
_
+
_
1
sC2
R
2
_
v
out
_
(1 +A
0
)
_
1
sC
1
R
1
_
+
_
1
sC
2
R
2
__
= −v
in
A
0
_
1
sC
2
R
2
_
v
out
v
in
= −A
0
1
sC2
R
2
(1 +A
0
)
_
1
sC1
R
1
_
+
_
1
sC2
R
2
_
Unity gain occurs when the numerator and denominator are the same (note that we can drop the
negative sign since we only care about the magnitude of the gain):
A
0
_
1
sC
2
R
2
_
= (1 +A
0
)
_
1
sC
1
R
1
_
+
_
1
sC
2
R
2
_
(A
0
− 1)
_
1
sC
2
R
2
_
= (1 +A
0
)
_
1
sC
1
R
1
_
_
1
sC2
R
2
_
_
1
sC1
R
1
_ =
A
0
+ 1
A
0
− 1
It is possible to obtain unity gain by choosing the resistors and capacitors according to the above
formula.
8.31
v
out
= −A
0
v
X
v
1
−v
X
R
2
+
v
2
−v
X
R
1
=
v
X
−v
out
R
F
v
out
R
F
+
v
1
R
2
+
v
2
R
1
=
v
X
R
1
R
2
R
F
v
out
= −A
0
(R
1
R
2
R
F
)
v
out
R
F
+
v
1
R
2
+
v
2
R
1
v
out
1 +A
0
(R
1
R
2
R
F
)
R
F
= −A
0
(R
1
R
2
R
F
)
v
1
R
2
+
v
2
R
1
v
out
= −A
0
(R
1
R
2
R
F
)
v1
R2
+
v2
R1
1 +A
0
(R1R2RF )
RF
= −A
0
R
F
(R
1
R
2
R
F
)
v1
R2
+
v2
R1
R
F
+A
0
(R
1
R
2
R
F
)
= −
v
1
R
2
+
v
2
R
1
[R
F
A
0
(R
1
R
2
R
F
)]
8.32 For A
0
= ∞, we know that v
+
= v
−
, meaning that no current ﬂows through R
P
. Thus, R
P
will have
no eﬀect on v
out
.
v
out
= −R
F
v
1
R
2
+
v
2
R
1
, A
0
= ∞
For A
0
< ∞, we have to include the eﬀects of R
P
.
v
out
= −A
0
v
X
v
X
=
v
1
−v
X
R
2
+
v
2
−v
X
R
1
+
v
out
−v
X
R
F
R
P
v
X
1
R
P
+
1
R
1
+
1
R
2
+
1
R
F
=
v
1
R
2
+
v
2
R
1
+
v
out
R
F
v
X
=
v
1
R
2
+
v
2
R
1
+
v
out
R
F
(R
1
R
2
R
F
R
P
)
v
out
= −A
0
v
1
R
2
+
v
2
R
1
+
v
out
R
F
(R
1
R
2
R
F
R
P
)
v
out
1 +
A
0
R
F
(R
1
R
2
R
F
R
P
)
= −A
0
v
1
R
2
+
v
2
R
1
(R
1
R
2
R
F
R
P
)
v
out
= −A
0
v
1
R
2
+
v
2
R
1
(R
1
R
2
R
F
R
P
)
1 +
A0
RF
(R
1
R
2
R
F
R
P
)
= −
v
1
R
2
+
v
2
R
1
R
F
A
0
(R
1
R
2
R
F
R
P
)
R
F
+A
0
(R
1
R
2
R
F
R
P
)
= −
v
1
R
2
+
v
2
R
1
[R
F
A
0
(R
1
R
2
R
F
R
P
)] , A
0
< ∞
8.33 We must ﬁnd v
out
for the following circuit:
v
1
R
2
v
2
R
1
+
v
X
−
R
F
v
out
R
out
−
−A
0
v
X
+
v
out
= −A
0
v
X
+
v
1
−v
X
R
2
+
v
2
−v
X
R
1
R
out
= −v
X
A
0
+
R
out
R
1
+
R
out
R
2
+R
out
v
1
R
2
+
v
2
R
1
v
X
= v
out
+
v
1
−v
X
R
2
+
v
2
−v
X
R
1
R
F
v
X
1
R
F
+
1
R
1
+
1
R
2
=
v
out
R
F
+
v
1
R
2
+
v
2
R
1
v
X
=
v
out
R
F
+
v
1
R
2
+
v
2
R
1
(R
1
R
2
R
F
)
v
out
= −
v
out
R
F
+
v
1
R
2
+
v
2
R
1
(R
1
R
2
R
F
)
A
0
+
R
out
R
1
+
R
out
R
2
+R
out
v
1
R
2
+
v
2
R
1
Grouping terms, we have:
v
out
1 +
(R
1
R
2
R
F
)
A
0
+
Rout
R1R2
R
F
= −
v
1
R
2
+
v
2
R
1
(R
1
R
2
R
F
)
A
0
+
R
out
R
1
R
2
+R
out
v
1
R
2
+
v
2
R
1
= −
v
1
R
2
+
v
2
R
1
(R
1
R
2
R
F
)
A
0
+
R
out
R
1
R
2
+R
out
v
out
= −R
F
v
1
R
2
+
v
2
R
1
R
out
+ (R
1
R
2
R
F
)
A
0
+
Rout
R1R2
R
F
+ (R
1
R
2
R
F
)
A
0
+
Rout
R1R2
8.34 We must ﬁnd v
out
for the following circuit:
v
1
R
2
v
2
R
1
R
in
+
v
X
−
R
P
R
F
v
out
−
−A
0
v
X
+
v
out
= −A
0
v
X
v
X
=
v
1
−v
X
1 +
RP
Rin
R
1
+
v
2
−v
X
1 +
RP
Rin
R
2
+
v
out
−v
X
1 +
RP
Rin
R
F
R
in
Grouping terms, we have:
v
X
1
R
in
+
1 +
R
P
R
in
1
R
1
R
2
R
F
=
v
1
R
2
+
v
2
R
1
+
v
out
R
F
v
X
(R
1
R
2
R
F
) +R
P
+R
in
R
in
(R
1
R
2
R
F
)
=
v
1
R
2
+
v
2
R
1
+
v
out
R
F
v
X
=
v
1
R
2
+
v
2
R
1
+
v
out
R
F
R
in
(R
1
R
2
R
F
)
(R
1
R
2
R
F
) +R
P
+R
in
v
out
= −A
0
v
1
R
2
+
v
2
R
1
+
v
out
R
F
R
in
(R
1
R
2
R
F
)
(R
1
R
2
R
F
) +R
P
+R
in
Grouping terms, we have:
v
out
1 +
A
0
R
F
R
in
(R
1
R
2
R
F
)
(R
1
R
2
R
F
) +R
P
+R
in
= −
v
1
R
2
+
v
2
R
1
A
0
R
in
(R
1
R
2
R
F
)
(R
1
R
2
R
F
) +R
P
+R
in
v
out
R
F
[(R
1
R
2
R
F
) +R
P
+R
in
] +A
0
R
in
(R
1
R
2
R
F
)
R
F
[(R
1
R
2
R
F
) +R
P
+R
in
]
= −
v
1
R
2
+
v
2
R
1
A
0
R
in
(R
1
R
2
R
F
)
(R
1
R
2
R
F
) +R
P
+R
in
Simplifying, we have:
v
out
= −
v
1
R
2
+
v
2
R
1
A
0
R
F
R
in
(R
1
R
2
R
F
)
R
F
[(R
1
R
2
R
F
) +R
P
+R
in
] +A
0
R
in
(R
1
R
2
R
F
)
8.35
I
D1
=
Vin
R1
V
in
> 0
0 V
in
< 0
Plotting I
D1
(t), we have
0
V
0
/R
1
I
D
1
(
t
)
−π/ω 0 π/ω
t
−V
0
0
V
0
V
i
n
(
t
)
=
V
0
c
o
s
(
ω
t
)
(
D
o
t
t
e
d
)
8.36
I
D1
=
Vin
R1
V
in
> 0
0 V
in
< 0
Plotting I
D1
(t), we have
0
V
0
/R
1
I
D
1
(
t
)
−π/ω 0 π/ω
t
−V
0
0
V
0
V
i
n
(
t
)
=
V
0
c
o
s
(
ω
t
)
(
D
o
t
t
e
d
)
8.37
V
Y
=
V
in
−V
D,on
V
in
< 0
V
DD
V
in
> 0
V
out
=
V
in
V
in
< 0
0 V
in
> 0
I
D1
=
Vin
R1
V
in
< 0
0 V
in
> 0
Plotting V
Y
(t) and V
out
(t), we have
−π/ω 0 π/ω
t
−V
0
0
V
0
V
DD
V
in
(t) = V
0
cos(ωt)
V
Y
(t)
V
out
(t)
Plotting I
D1
(t), we have:
0
V
0
/
R
1
I
D1
(t)
−
π
/
ω
0
π
/
ω
t
−
V
0
0 V
0
V
in
(t) = V
0
cos(ωt) (Dotted)
8.38 Since the negative feedback loop is never broken (even when the diode is oﬀ, R
P
provides negative
feedback), V
+
= V
−
will always hold, meaning V
X
= V
in
.
We must determine when D
1
turns on/oﬀ to determine V
Y
. We know that for V
in
< 0, the diode will
be oﬀ, and V
X
will follow V
in
. As V
in
begins to go positive, the diode will remain oﬀ until
V
in
R
P
R
1
> V
D,on
Once the diode turns on, V
Y
will be ﬁxed at V
in
+V
D,on
. Thus, we can write:
V
X
= V
in
V
Y
=
V
in
1 +
RP
R1
V
in
< V
D,on
R1
RP
V
in
+V
D,on
V
in
> V
D,on
R1
RP
Plotting V
Y
(t) and V
out
(t), we have
−π/ω 0 π/ω
t
−V
0
(1 + R
P
/R
1
)
−V
0
0
V
0
V
0
+ V
D,on
V
in
(t) = V
0
cos(ωt)
V
X
(t)
V
Y
(t)
8.40 Note that although in theory the output is unbounded (i.e., by Eq. (8.66), we can take the logarithm
of an arbitrarily small positive number), in reality the output will be limited by the positive supply
rail, as shown in the following plot.
−1 0 R
1
I
S
1
V
in
(V)
V
DD
0
−1
V
out
V
X
8.42 When V
in
> 0, the feedback loop will be broken, and the output will go to the positive rail.
When V
in
< 0, we have:
I
C
= −
V
in
R
1
= I
S
e
VBE/VT
= I
S
e
−Vout/VT
V
out
= −V
T
ln
−
V
in
R
1
I
S
This gives us the following plot of V
out
vs. V
in
:
−1 0 −R
1
I
S
1
V
in
(V)
V
DD
0
V
o
u
t
(
V
)
Note that this circuit fails to behave as a noninverting logarithmic ampliﬁer.
8.44 (a)
V
out
= −V
T
ln
V
in
R
1
I
S
−0.2 V = −V
T
ln
1 V
R
1
I
S
R
1
I
S
= 456 µV
(b)
A
v
=
dV
out
dV
in
Vin=1 V
= −
V
T
V
in
Vin=1 V
= −0.026
8.45 When V
in
< V
TH
, the output goes to the positive rail. When V
in
> V
TH
, we have:
I
D
=
V
in
−V
TH
R
1
V
GS
= −V
out
= V
TH
+
2I
D
W
L
µ
n
C
ox
V
out
= −V
TH
−
2 (V
in
−V
TH
)
R
1
W
L
µ
n
C
ox
dV
out
dV
in
= −
1
2
R
1
W
L
µ
n
C
ox
2 (V
in
−V
TH
)
2
R
1
W
L
µ
n
C
ox
= −
1
2R
1
W
L
µ
n
C
ox
(V
in
−V
TH
)
, V
in
> V
TH
8.46 When V
in
> 0, the output goes to the negative rail. When V
in
< 0, we have:
I
D
= −
V
in
R
1
V
SG
= V
out
= V
TH
 +
2 I
D

W
L
µ
p
C
ox
V
out
= V
TH
+
−
2V
in
R
1
W
L
µ
p
C
ox
, V
in
< 0
8.49 We model an input oﬀset with a series voltage source at one of the inputs.
−
+
−
+
V
os
R
2
−
+
V
in
R
1
V
out
V
out
= V
in
−
V
in
−V
os
R
2
(R
1
+R
2
)
= V
in
1 −
R
1
+R
2
R
2
+V
os
R
1
+R
2
R
2
= −
R
1
R
2
V
in
+
1 +
R
1
R
2
V
os
Note that even when V
in
= 0, V
out
= (1 +R
1
/R
2
) V
os
.
8.54 Let V
in
= 0.
V
+
= −I
B1
(R
1
R
2
) = −(I
B2
+ ∆I) (R
1
R
2
) = V
−
V
out
= V
−
+
I
B2
+
V
−
R
2
R
1
= −(I
B2
+ ∆I) (R
1
R
2
) +
I
B2
−
(I
B2
+ ∆I) (R
1
R
2
)
R
2
R
1
= −(I
B2
+ ∆I) (R
1
R
2
)
1 +
R
1
R
2
+I
B2
R
1
= −∆IR
1
If the magnitude of the error must be less than ∆V , we have:
∆IR
1
< ∆V
R
1
<
∆V
∆I
Note that this does not depend on R
2
.
8.57
V
out
= −
A
0
1 +
s
ω0
V
−
V
−
= V
in
+
V
out
−V
in
R
1
+
1
sC1
R
1
V
out
= −
A
0
1 +
s
ω0
V
in
+
V
out
−V
in
R
1
+
1
sC1
R
1
V
out
1 +
A
0
1 +
s
ω0
R
1
R
1
+
1
sC1
=
A
0
1 +
s
ω0
V
in
R
1
R
1
+
1
sC1
−1
V
out
1 +
s
ω0
R
1
+
1
sC1
+A
0
R
1
1 +
s
ω0
R
1
+
1
sC1
= −V
in
A
0
1
sC1
1 +
s
ω0
R
1
+
1
sC1
V
out
V
in
= −
A
0
1
sC1
1 +
s
ω0
R
1
+
1
sC1
+A
0
R
1
= −
A
0
1 +
s
ω0
(1 +sR
1
C
1
) +sA
0
R
1
C
1
= −
A
0
1 +s
R
1
C
1
+
1
ω0
+A
0
R
1
C
1
+s
2
R1C1
ω0
= −
A
0
1 +s
(1 +A
0
) R
1
C
1
+
1
ω0
+s
2
R1C1
ω0
If ω
0
≫
1
R1C1
, we have:
V
out
V
in
= −
1
1
A0
+s
1 +
1
A0
R
1
C
1
+
1
ω0
+s
2
R1C1
A0ω0
= −
1
1
A0
+s
1 +
1
A0
R
1
C
1
+s
2
R1C1
A0ω0
≈ −
1
sR
1
C
1
+s
2
R1C1
A0ω0
(assuming A
0
≫1)
= −
1
sR
1
C
1
1 +
s
A0ω0
8.61 Let E refer to the gain error.
R
1
R
2
= 8
R
1
= 8 kΩ
R
2
= 1 kΩ
v
out
v
in
= −
R
1
R
2
A
0
−
Rout
R1
1 +
Rout
R2
+ A
0
+
R1
R2
(Eq. 8.99)
= −
R
1
R
2
(1 − E)
E = 1 −
A
0
−
Rout
R1
1 +
Rout
R2
+ A
0
+
R1
R2
= 0.1 %
A
0
= 9103
Note that we can pick any R
1
, R
2
such that their ratio is 8 (i.e., this solution is not unique). However,
A
0
will change depending on the values chosen.
8.66
V
out
= −V
T
ln
V
in
R
1
I
S
dV
out
dV
in
= −V
T
R
1
I
S
V
in
1
R
1
I
S
= −
V
T
V
in
No, it is not possible to satisfy both requirements. As shown above,
dVout
dVin
=
VT
Vin
, meaning for a
speciﬁed temperature and input, the gain is ﬁxed. Assuming we could ﬁx the temperature as part of
the design, we could still only meet one of the two constraints, since the temperatures at which the
constraints are met are not equal.